RELATIONSHIP BETWEEN TOLERANCE ATTITUDES WITH THE LEARNING RESULTS OF CLASS VII STUDENTS IN LEARNING IPA IN SMP NEGERI 8 JAMBI CITY - Sari, Rizki Intan; Andika, Gustia (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2019)
The purpose of this study was to determine the relationship between tolerance and learning outcomes of students in Junior High School 8 Kota Jambi. This type of research is a correlation study with a descriptive approach. This research was conducted in classes VII B and VII F. When the study was conducted in the even semester of the 2018/2019 academic year. The number of sample respondents in this study were 61 students. Data collection techniques in this study used a questionnaire technique to obtain student character data consisting of 25 items then test techniques in the form of multiple choice questions consisting of 30 items used to collect data. This research uses quantitative research methods, which consist of quantitative data and analysis using correlation analysis techniques. The results of the analysis conducted by the researcher showed that tolerance attitudes were significantly related to the learning outcomes of students of class VII B and VII F of Junior High School 8 Kota Jambi. This can be proven by showing a significant value of <0.05, which is equal to 0,000 and Person Correlation of 0,956> 0,05. To find out the significance of the relationship between tolerance character education and student learning outcomes can be done by looking at the significance value, where the test tests the opinion the significance level is smaller than 0.05 (95% confidence level), then a significant relationship between the independent variable and dependent variable is needed. Based on the calculation results a significant value is smaller than 0.05, which is 0,000 <0.05. Therefore, it can be recognized that there is a relationship between education tolerance and learning outcomes of students of class VII B and VII F in Junior High School 8 Kota Jambi.